Gender, conflict and the environment: Surfacing connections in international humanitarian law - Martín, Ana; O’Rourke, Catherine (International Review of the Red Cross, 2024)
Both gender and the environment have traditionally been positioned at the periphery of international humanitarian law (IHL). In recent decades, there has been important progress in moving both concerns closer to its centre; to date, however, an understanding of the intersection of gender and the environment in the legal regulation of armed conflict remains largely underdeveloped. Nevertheless, as the present article documents, there are important similarities in strategies pursued to advance both gender and the environment from the periphery to the mainstream of IHL, namely: first, a focus on sources of IHL, in particular concretizing arguably limited specific treaty content with interpretive guidance and implementation frameworks; second, a conceptual critique of prevailing definitions of “harm” in IHL; and third, advancing, through close empirical documentation and household-level analysis of conflict’s effects, understandings of harm that capture so-called “second-round” effects of conflict. Recognizing these important affinities between gender and environment work in IHL, this article draws on these insights to propose a typology of gendered environmental harm in conflict. The article concludes with proposals for enhancing the legal and operational capture under IHL of the gender–conflict–environment nexus.
Keywords: gender; environment; harm; armed conflict; nexus; international humanitarian law; Scopus; Emerging